Optimized Dosing Schedule Based on Circadian Dynamics of Mouse Breast Cancer Stem Cells Improves the Antitumor Effects of Aldehyde Dehydrogenase Inhibitor - Matsunaga, Naoya; Ogino, Takashi; Hara, Yukinori; Tanaka, Takahiro; Koyanagi, Satoru; Ohdo, Shigehiro (Cancer research (Chicago, Ill.), 2018)
Although malignant phenotypes of triple-negative breast cancer (TNBC) are subject to circadian alterations, the role of cancer stem cells (CSC) in defining this circadian change remains unclear. CSC are often characterized by high aldehyde dehydrogenase (ALDH) activity, which is associated with the malignancy of cancer cells and is used for identification and isolation of CSC. Here, we show that the population of ALDH-positive cells in a mouse 4T1 breast tumor model exhibits pronounced circadian alterations. Alterations in the number of ALDH-positive cells were generated by time-dependent increases and decreases in the expression of Aldh3a1. Importantly, circadian clock genes were rhythmically expressed in ALDH-negative cells, but not in ALDH-positive cells. Circadian expression of Aldh3a1 in ALDH-positive cells was dependent on the time-dependent release of Wingless-type mmtv integration site family 10a (WNT10a) from ALDH-negative cells. Furthermore, antitumor and antimetastatic effects of ALDH inhibitor N,N-diethylaminobenzaldehyde were enhanced by administration at the time of day when ALDH activity was increased in 4T1 tumor cells. Our findings reveal a new role for the circadian clock within the tumor microenvironment in regulating the circadian dynamics of CSC. These results should enable the development of novel therapeutic strategies for treatment of TNBC with ALDH inhibitors. Significance: This seminal report reveals that circadian dynamics of CSC are regulated by the tumor microenvironment and provides a proof of principle of its implication for chronotherapy in TNBC. Cancer Res; 78(13); 3698–708. ©2018 AACR.